Carbon fiber reinforced acid and alkali resistant PPS material and preparation method thereof

By combining oxidized carbon fibers with star-shaped phenyl sulfide compounds to prepare modified carbon fibers and adding modified glass fibers to PPS materials, the shortcomings of existing materials in terms of mechanical properties and acid and alkali resistance are solved, and the material performance is significantly improved.

CN119570081AActive Publication Date: 2025-03-07GUANGDONG YONGXINHUA NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411791903.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing carbon fiber reinforced PPS materials still need to be further improved in terms of mechanical properties and acid and alkali resistance to meet the application needs in high-performance and extreme chemical environments.

Method used

Modified carbon fibers are prepared by combining oxidized carbon fibers with star-shaped phenyl sulfide compounds, and modified glass fibers are added to the PPS material to improve interface compatibility and bonding strength, thereby improving the mechanical properties and acid and alkali resistance of the material.

Benefits of technology

It has achieved a significant improvement in the mechanical properties and acid and alkali resistance of PPS materials, enhanced the stability and dispersion of the materials, and is suitable for applications in high-performance and extreme chemical environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175511160000021
    Figure BDA0005175511160000021
  • Figure BDA0005175511160000041
    Figure BDA0005175511160000041
  • Figure BDA0005175511160000051
    Figure BDA0005175511160000051
Patent Text Reader

Abstract

The invention provides a carbon fiber reinforced acid and alkali resistant PPS material. The carbon fiber reinforced acid and alkali resistant PPS material comprises the following components in parts by mass: 40-80 parts of PPS, 5-10 parts of modified carbon fiber, 1-5 parts of modified glass fiber, 1-5 parts of a coupling agent, 1-5 parts of an antioxidant and 1-10 parts of a lubricant. The modified carbon fiber provided by the invention has a polyphenylene sulfide structure and a star-shaped structure, has good compatibility with other components, and can form a more regular and compact three-dimensional net structure with other components, so that the stability of a product is enhanced, and a plurality of properties such as mechanical properties, acid and alkali resistance and the like are improved. Meanwhile, by introducing a polyphenylene sulfide structure and a benzyl alcohol structure into the modified glass fiber, the interfacial compatibility and bonding strength are effectively improved, the compatibility with other components is enhanced, and the components are combined more tightly, so that the dispersity and stability of the system are further enhanced, and the performance of the PPS material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a carbon fiber reinforced acid- and alkali-resistant PPS material and a preparation method thereof. Background Art

[0002] As a high-performance engineering plastic, polyphenylene sulfide (PPS) plays an important role in many fields such as aerospace, electronics and automobile industries due to its excellent properties such as high temperature resistance, corrosion resistance, insulation and low moisture absorption. However, with the advancement of science and technology and industrial development, the performance requirements for PPS materials are increasing. Although PPS itself has a series of excellent properties, its inherent performance limitations still exist, which to a certain extent restricts its application potential in a wider range of fields. Therefore, modifying and enhancing PPS materials to meet the needs of higher performance has become an important research direction in the field of materials science.

[0003] In the existing technical field, it has become a common practice to modify PPS to improve its performance. Among them, the technology of using carbon fiber to reinforce PPS materials is particularly favored. This composite material has shown significant performance improvements in many key areas such as mechanical strength, thermal stability, corrosion resistance, aging resistance and flame retardancy. Through the reinforcement of carbon fiber, the toughness and strength of PPS have been significantly enhanced, making it the preferred composite material in high-end application fields such as aerospace. In addition, the addition of carbon fiber has also significantly improved the impact resistance of PPS composite materials, which can effectively absorb external impact energy, thereby improving the material's load-bearing capacity.

[0004] However, despite the progress made in the performance of carbon fiber reinforced PPS materials, they still face some challenges, such as mechanical properties and acid and alkali resistance, which still need to be further improved to meet the application requirements of high performance and extreme chemical environments. Therefore, the development of a carbon fiber reinforced PPS material with both excellent mechanical properties and excellent acid and alkali resistance is of great significance to expand its application range and enhance its market competitiveness.

[0005] In summary, it is necessary to develop a new technical solution to solve the problems existing in the prior art. Summary of the invention

[0006] The present invention provides a carbon fiber reinforced acid and alkali resistant PPS material, which is prepared from PPS, modified glass fiber, star-shaped benzene sulfide compound, modified carbon fiber, etc. The present invention combines oxidized carbon fiber and star-shaped benzene sulfide compound to obtain modified carbon fiber, and adds it to PPS material, which can effectively improve the performance of PPS material. On the one hand, the modified carbon fiber has a benzene sulfide structure, has good compatibility with components with similar structures such as PPS and modified glass fiber, and can effectively improve the dispersibility of the components; on the other hand, the modified carbon fiber has a star structure, which makes the modified carbon fiber have a larger specific surface area, and a plurality of side chains radiating from the central core, which can enhance the contact area between the modified carbon fiber and other components, and at the same time has multiple active sites, which can form a more regular and tight three-dimensional network structure with other components, enhance the stability of the product, and achieve the improvement of mechanical properties, acid and alkali resistance and other properties. At the same time, the present invention introduces a benzyl sulfide structure and a benzyl alcohol structure into the modified glass fiber, thereby effectively improving the interface compatibility and bonding strength, enhancing the compatibility with other components, and making the combination between the components tighter, thereby further enhancing the dispersibility and stability of the system and improving the performance of the PPS material.

[0007] One object of the present invention is to provide a carbon fiber reinforced acid and alkali resistant PPS material, wherein the carbon fiber reinforced acid and alkali resistant PPS material comprises the following components in parts by mass:

[0008]

[0009] in,

[0010] The modified carbon fiber is a star-shaped benzene sulfide compound modified carbon fiber;

[0011] The modified glass fiber is a hydroxylated glass fiber, which is partially grafted with 3,3'-dicarboxyl diphenyl disulfide and partially grafted with p-hydroxybenzoic acid.

[0012] Furthermore, the coupling agent is selected from one or more of silane, titanate, phosphate, chromium complex or zirconium coupling agent.

[0013] Furthermore, the antioxidant is selected from one or more of antioxidant 245, antioxidant 1076 or antioxidant 168.

[0014] Furthermore, the lubricant is selected from one or more of zinc stearate or silicone powder.

[0015] Another object of the present invention is to provide a method for preparing the above-mentioned carbon fiber reinforced acid and alkali resistant PPS material, comprising the following steps:

[0016] S1, immersing the carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, heating and stirring to react, to obtain oxidized carbon fiber;

[0017] S2, mixing p-aminothiophenol with acetic anhydride, heating and stirring to react, to obtain p-acetaminothiophenol; mixing the p-acetaminothiophenol with hexabromobenzene, adding N,N-dimethylformamide under inert gas and low temperature conditions, stirring, and then adding sodium hydride to react; after the reaction is completed, adding HCl solution under low temperature conditions, and then adding water to precipitate, to obtain a star-shaped benzene sulfide compound;

[0018] S3, blending the oxidized carbon fiber and the star-shaped benzene sulfide compound, and subjecting the mixture to ultrasonic heating reaction to obtain modified carbon fiber;

[0019] S4, soaking the glass fiber in hydrogen peroxide, heating and stirring to react, to obtain hydroxylated glass fiber; blending the hydroxylated glass fiber with 3,3'-dicarboxyl diphenyl disulfide, ultrasonic heating reaction, to obtain an intermediate product; blending the intermediate product with p-hydroxybenzoic acid, ultrasonic heating reaction, to obtain modified glass fiber;

[0020] S5. Blend the modified PPS, coupling agent, lubricant and antioxidant, and feed them from the main feeding port of the extruder; feed the modified carbon fiber from the first side feeding port of the extruder barrel; feed the modified glass fiber from the second side feeding port of the extruder barrel; and blend and granulate them in the extruder to obtain the carbon fiber reinforced acid and alkali resistant PPS material.

[0021] Furthermore, in step S2, the mass ratio of p-aminothiophenol to acetic anhydride is 1:(1-3); the mass ratio of p-acetaminothiophenol, hexabromobenzene and sodium hydride is 1:(2-4):(0.1-0.5).

[0022] Furthermore, in step S4, the mass ratio of the hydroxylated glass fiber, 3,3'-dicarboxy diphenyl disulfide and p-hydroxybenzoic acid is 1:(0.5-2):(0.1-1).

[0023] Furthermore, in step S1, the heating temperature is 50-70°C.

[0024] Furthermore, in step S2, the heating temperature is 50-70°C.

[0025] Furthermore, in step S3, the heating temperature is 50-70°C.

[0026] Furthermore, in step S4, the heating temperature is 60-100°C.

[0027] The present invention has the following beneficial effects:

[0028] The present invention obtains modified carbon fiber by mixing and reacting oxidized carbon fiber and star-shaped benzene sulfide compound with carboxyl terminal group, and adds it to PPS material, which can effectively improve the performance of PPS material. On the one hand, the modified carbon fiber has a benzene sulfide structure, and has good compatibility with components with similar structures such as PPS and modified glass fiber, and can effectively improve the dispersibility of the components; on the other hand, the modified carbon fiber has a star-shaped structure, which makes the modified carbon fiber have a larger specific surface area, and multiple side chains radiating from the central core, which can enhance the contact area between the modified carbon fiber and other components, and has multiple active sites, which can form a more regular and tight three-dimensional network structure with other components, strengthen the stability of the product, and realize the improvement of various properties such as mechanical properties and acid and alkali resistance. At the same time, the present invention effectively improves the interfacial compatibility and bonding strength by introducing benzene sulfide structure and benzyl alcohol structure in modified glass fiber, enhances the compatibility with other components, and makes the combination between components more closely, thereby further enhancing the dispersibility and stability of the system and improving the performance of PPS material. DETAILED DESCRIPTION

[0029] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0030] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0031] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values ​​that vary depending on the desired properties to be obtained by the present invention.

[0032] The following raw materials are used in the examples and comparative examples of the present invention:

[0033] PPS was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with an average molecular weight of 10,000.

[0034] Glass fiber was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a brand number of F864783.

[0035] Carbon fiber was purchased from Toray New Materials (Guangdong) Co., Ltd. with the brand name T700.

[0036] The coupling agent is silane coupling agent KH550.

[0037] The lubricant is zinc stearate.

[0038] The antioxidant is antioxidant 245.

[0039] Example 1

[0040] A carbon fiber reinforced acid and alkali resistant PPS material, the carbon fiber reinforced acid and alkali resistant PPS material comprising the following components in parts by mass:

[0041]

[0042] The preparation method of the above carbon fiber reinforced acid and alkali resistant PPS material comprises the following steps:

[0043] S1. Soak the carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (concentrated sulfuric acid: concentrated nitric acid = 3:1, v / v), stir and react for 4 hours at 60° C., filter, wash and dry to obtain oxidized carbon fiber;

[0044] S2. Add 15.5g of p-aminothiophenol to 45mL of distilled water, heat to 60°C, then add 18g of acetic anhydride under stirring and react for 15min, cool, filter, wash and dry to obtain p-acetaminothiophenol; add 1.2g of the p-acetaminothiophenol and 2.85g of hexabromobenzene to a reaction bottle equipped with a condenser, mix, evacuate and fill with nitrogen, place in an ice bath, turn on the condensed water, then add 25mL of dried N,N-dimethylformamide, stir, add 0.35g of sodium hydride, turn off the condensed water after the temperature of the reaction system drops to room temperature, evacuate the ice bath, and stir at room temperature for 3 days. After the reaction is completed, cool it to 0°C, add 50mL of a freshly prepared 1mol / L ice HCl aqueous solution, then pour it into 200mL of secondary distilled water, precipitate, filter, wash and dry the precipitate to obtain a star-shaped benzene sulfide compound;

[0045] S3, using ethanol as a solvent, blending the oxidized carbon fiber and the star-shaped benzene sulfide compound (oxidized carbon fiber: star-shaped benzene sulfide compound=1:1, m / m), stirring and reacting at 70° C. for 8 h, filtering, washing, and drying to obtain a modified carbon fiber;

[0046] S4, soak 1g of glass fiber in 10mL of hydrogen peroxide, stir evenly, reflux at 105°C for 3h, filter, wash, and dry to obtain hydroxylated glass fiber; use methanol as solvent, blend 5g of the hydroxylated glass fiber with 5g of 3,3'-dicarboxyl diphenyl disulfide, ultrasonically react at 80°C for 10h, filter, wash, and dry to obtain an intermediate product; use methanol as solvent, blend the intermediate product with 3g of p-hydroxybenzoic acid, ultrasonically react at 80°C for 10h, filter, wash, and dry to obtain modified glass fiber;

[0047] S5. Blend PPS, coupling agent, antioxidant and lubricant according to the above-mentioned mass fractions, and feed them from the main feeding port of the extruder; feed the modified carbon fiber from the first side feeding port of the extruder barrel; feed the modified glass fiber from the second side feeding port of the extruder barrel; melt extrude at 310°C, the screw extruder speed is 500rpm, the pressure is 2MPa, and after melt extrusion and granulation, the carbon fiber reinforced acid and alkali resistant PPS material is obtained.

[0048] Example 2

[0049] A carbon fiber reinforced acid and alkali resistant PPS material, the carbon fiber reinforced acid and alkali resistant PPS material comprising the following components in parts by mass:

[0050]

[0051] The preparation method of the above carbon fiber reinforced acid and alkali resistant PPS material is the same as that in Example 1.

[0052] Example 3

[0053] A carbon fiber reinforced acid and alkali resistant PPS material, the carbon fiber reinforced acid and alkali resistant PPS material comprising the following components in parts by mass:

[0054]

[0055] The preparation method of the above carbon fiber reinforced acid and alkali resistant PPS material is the same as that in Example 1.

[0056] Comparative Example 1

[0057] A carbon fiber reinforced acid- and alkali-resistant PPS material. The difference between this comparative example and Example 1 is that in step S5, the mass of the modified carbon fiber is replaced by a mixture of carbon fiber and star-shaped benzene sulfide compound (carbon fiber: star-shaped benzene sulfide compound = 1:1, m / m), and the amounts of other components and the preparation method are the same as those in Example 1.

[0058] Comparative Example 2

[0059] A carbon fiber reinforced acid- and alkali-resistant PPS material. The difference between this comparative example and Example 1 is that in step S5, the modified glass fiber and other qualities are replaced by the intermediate product, and the amounts of other components and the preparation method are the same as those in Example 1.

[0060] Comparative Example 3

[0061] A carbon fiber reinforced acid- and alkali-resistant PPS material. The difference between this comparative example and Example 1 is that in step S4, the reaction between hydroxylated glass fiber and 3,3'-dicarboxy diphenyl disulfide is not carried out, and the amounts of other components and the preparation method are the same as those in Example 1.

[0062] Test Case

[0063] The carbon fiber reinforced acid and alkali resistant PPS materials prepared in Examples 1-3 and Comparative Examples 1-3 were dried in an oven at 140°C for 4 hours and then injection molded. The injection molded specimens were ASTM specimens, and the injection molding temperatures were as follows: feeding section: 280-290°C; second section: 300-310°C; third section: 310-320°C; nozzle: 310-315°C; mold temperature of the injection molded specimens: 120°C.

[0064] The above injection molded specimens were taken for the following performance tests.

[0065] Test method:

[0066] Tensile strength: tested according to ISO527 standard;

[0067] Impact strength: tested according to ISO179 standard;

[0068] Strength retention rate: The retention rate of tensile strength after the above injection molded specimens are immersed in acid / alkali for 15 days at 93°C.

[0069] The test results are shown in Table 1.

[0070] Table 1 Performance test results

[0071]

[0072] It can be seen from the above test results that the carbon fiber reinforced acid and alkali resistant PPS materials of Examples 1-3 of the present invention have good mechanical properties and excellent tensile strength retention under various acid and alkali conditions. All capabilities are significantly better than those of Comparative Examples 1-3 of replaced components, proving that in the technical scheme of the present invention, modified carbon fibers, modified glass fibers, star-shaped benzene sulfide compounds and other components can interact with each other, enhance the dispersibility and stability of the system, and achieve improvements in the product's mechanical properties, acid and alkali resistance and other properties.

[0073] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0074] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A carbon fiber reinforced acid and alkali resistant PPS material, characterized in that: The carbon fiber reinforced acid and alkali resistant PPS material comprises the following components in parts by mass: in, The modified carbon fiber is a star-shaped benzene sulfide compound modified carbon fiber; The modified glass fiber is a hydroxylated glass fiber, which is partially grafted with 3,3'-dicarboxyl diphenyl disulfide and partially grafted with p-hydroxybenzoic acid.

2. The carbon fiber reinforced acid and alkali resistant PPS material according to claim 1, characterized in that: The coupling agent is selected from one or more of silane, titanate, phosphate, chromium complex or zirconium coupling agent.

3. The carbon fiber reinforced acid and alkali resistant PPS material according to claim 1, characterized in that: The antioxidant is selected from one or more of antioxidant 245, antioxidant 1076 or antioxidant 168.

4. The method for preparing the carbon fiber reinforced acid and alkali resistant PPS material according to any one of claims 1 to 3, characterized in that: The steps include: S1, immersing the carbon fiber in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, heating and stirring to react, to obtain oxidized carbon fiber; S2, mixing p-aminothiophenol with acetic anhydride, heating and stirring to react, to obtain p-acetaminothiophenol; mixing the p-acetaminothiophenol with hexabromobenzene, adding N,N-dimethylformamide under inert gas and low temperature conditions, stirring, and then adding sodium hydride to react; after the reaction is completed, adding HCl solution under low temperature conditions, and then adding water to precipitate, to obtain a star-shaped benzene sulfide compound; S3, blending the oxidized carbon fiber and the star-shaped benzene sulfide compound, and subjecting them to ultrasonic heating reaction to obtain modified carbon fiber; S4, soaking the glass fiber in hydrogen peroxide, heating and stirring to react, to obtain hydroxylated glass fiber; blending the hydroxylated glass fiber with 3,3'-dicarboxyl diphenyl disulfide, ultrasonic heating reaction, to obtain an intermediate product; blending the intermediate product with p-hydroxybenzoic acid, ultrasonic heating reaction, to obtain modified glass fiber; S5. Blend the modified PPS, coupling agent, lubricant and antioxidant, and feed them from the main feeding port of the extruder; feed the modified carbon fiber from the first side feeding port of the extruder barrel; feed the modified glass fiber from the second side feeding port of the extruder barrel; and blend and granulate them in the extruder to obtain the carbon fiber reinforced acid and alkali resistant PPS material.

5. The method for preparing the carbon fiber reinforced acid and alkali resistant PPS material according to claim 4, characterized in that: In step S2, the mass ratio of p-aminothiophenol to acetic anhydride is 1:(1-3); the mass ratio of p-acetaminothiophenol, hexabromobenzene and sodium hydride is 1:(2-4):(0.1-0.5).

6. The method for preparing the carbon fiber reinforced acid and alkali resistant PPS material according to claim 4, characterized in that: In step S4, the mass ratio of the hydroxylated glass fiber, 3,3'-dicarboxy diphenyl disulfide and p-hydroxybenzoic acid is 1:(0.5-2):(0.1-1).

7. The method for preparing the carbon fiber reinforced acid and alkali resistant PPS material according to claim 4, characterized in that: In step S1, the heating temperature is 50-70°C.

8. The method for preparing the carbon fiber reinforced acid and alkali resistant PPS material according to claim 4, characterized in that: In step S2, the heating temperature is 50-70°C.

9. The method for preparing the carbon fiber reinforced acid and alkali resistant PPS material according to claim 4, characterized in that: In step S3, the heating temperature is 50-70°C.

10. The method for preparing the carbon fiber reinforced acid and alkali resistant PPS material according to claim 4, characterized in that: In step S4, the heating temperature is 60-100°C.

Citation Information

Patent Citations

  • Preparation method of modified carbon fiber reinforced nylon particle

    CN111574731A

  • Carbon fiber reinforced polyphenylene sulfide composite material and preparation method thereof

    CN113265145A

  • Polyphenylene sulfide composition and preparation method thereof

    CN113861687A

  • High-temperature-resistant nano injection-molded PPS composite material and preparation method thereof

    CN115637047A

  • Impact-resistant polyphenylene sulfide composition and its production

    JP1997263676A

Cited By

  • Nano indium-iron microcrystalline adhesive and curing process

    CN120442199A

  • Graphite-filled polyphenylene sulfide composite material, heat conduction pipe and preparation method

    CN121086526A